Pure red cell aplasia due to antibody against erythropoietin in hemodialysis patients - Maryam Rahbar; Zahra Chitsazian; Firoozeh Abdoli; Seyed-Masoud Moeini Taba; Hosein Akbari (Society of Diabetic Nephropathy Prevention, 2017)
Background: Anemia is a common complication of chronic renal failure due to reduce erythropoietin production by kidneys. Anemia treated with recombinant human erythropoietin (rHu-EPO). Pure red cell aplasia (PRCA) due to antibody productionagainst rHu-EPO is a rare but major complication of this drug. Objectives: The aim of this study was to determine the prevalence of PRCA due to antibodies in dialysis patients with resistant anemia who received erythropoietin. Patients and Methods: We studied 128 under maintenance hemodialysis patients more than 3 month in Kashan. In patients with anemia who received erythropoietin with dose requirements based on weight and anemia and without any another cause for anemia, evaluate for PRCA and anti-rHu-EPO antibody level were measured by ELISA. Results: In this research, 75 patients (58.6%) were male and 53 patients (41.4%) were female. The mean age of the patients was 59.05 ± 16.66 years. The result of analysis showed that 55 (43%) patients had anemia with hemoglobin level less than 10 mg/dL. Only 3 patients had PRCA and antibodies against erythropoietin in serum. There were no correlation between age, gender, cause of renal failure, hemodialysis duration, hemoglobin level, rHu-EPO dose and levels of anti-rHu-EPO antibody serum value. Conclusions: The result of this study indicated that administration of rHu-EPO in dialysis patients afflicted to kidney failure may cause PRCA especially through intravenous injection. However, this change is not statistically significant.